Alice’s Jar - Anna Montebugnoli (Journal of Interdisciplinary History of Ideas, 2025)
Essay-review on a series of books published in recent years, all of which share a clear common core: ruins (Schnapp, Une histoire universelle des ruines. Des origines aux Lumières, 2020; it. transl. Storia universale delle rovine. Dalle origini all'età dei Lumi, 2023; Stewart, The Ruins Lesson. Meaning and Material in Western Culture, 2020; Marcheschi, Storie naturali delle rovine. Forme e oggetti del tempo nella Francia dei philosophes, 2023)